The work of bus drivers and their contribution to excellence in public transportation - Claudio Marcelo Brunoro; Laerte Idal Sznelwar; Ivan Bolis; Julia Abrahao (Production)
The article is the result of a survey aimed at analyzing the work of bus drivers for a collective urban transportation company that is considered a benchmark. The research sought to understand how the company could maintain a policy capable of reconciling the quality of public transportation with working conditions that are compatible with the professional development, comfort and health of the workers. The ergonomic work analysis methodology was adopted as a guide. The results show that one of the pillars of excellence achieved by this company is the quality of the work performed by their drivers, which is guided by the organizational values that permeate the organization. The driver plays a role in regulating the system by serving the population and providing mobility. Their activity is controlled by a series of interdependent variables, such as the demands for conducting the vehicle and the relationship with others.